Morphometric analysis of a population of diplopods of the genus Rhinocricus Karsch, 1881 - Calligaris, Izabela Braggião [UNESP]; Boccardo, L.; Sanches, M. R.; Fontanetti, C. S. [UNESP] (My University, 2005)
Diplopods belonging to the subclass Helminthomorpha may present one or both leg pairs of the seventh diplosegment modified into structures that aid copulation, called gonopods. These structures are used as a taxonomic trait for the description of most species. In the genus Rhinocricus these structures are closely similar, so that it is difficult to distinguish species only on the basis of this trait. Two species, R. padbergi and R. varians, are found in the same habitat and present gonopods practically identical in shape; together they present a broad colour gradient, ranging from dark brown to light beige. Morphometric data for individuals of the experimental group were submitted to ANOVA and MANOVA, using Hotelling-Lawley Trace and generalized Mahalanobis distances (D 2) tests. The results demonstrated a relationship between size and colour, with darker individuals being larger. On the basis of this preliminary analysis, we may suggest that the two species are distinct since dark individuals are distant from medium- and light-coloured individuals according to the D 2 values. This seems to indicate a possible polymorphism of individuals belonging to R. padbergi which present close proximity in the values obtained. In all analyses, we observed that the main variables were diameter, length and telson size.
Keywords: Diplopoda; Morphometry; Multivariated statistic; Rhinocricus; Taxonomy; analysis of variance; colorimetry; controlled study; data analysis; experimentation; genetic polymorphism; genus; helminth; morphometrics; multivariate analysis of variance; nonhuman; Rhinocricus padbergi; Rhinocricus varians; species difference; statistical analysis; Animal Structures; Animals; Arthropods; Body Weight; Brazil; Copulation; Female; Genitalia, Female; Genitalia, Male; Male; Organ Size; Pigmentation; Population; Sex Characteristics; Species Specificity; Helminthomorpha; Vermes